2012
DOI: 10.1002/cne.23175
|View full text |Cite
|
Sign up to set email alerts
|

Brain sources of inhibitory input to the rat rostral ventrolateral medulla

Abstract: The rostral ventrolateral medulla (RVLM) contains neurons critical for cardiovascular, respiratory, metabolic, and motor control. The activity of these neurons is controlled by inputs from multiple identified brain regions; however, the neurochemistry of these inputs is largely unknown. Gamma-aminobutyric acid (GABA) and enkephalin tonically inhibit neurons within the RVLM. The aim of this study was to identify all brain regions that provide GABAergic or enkephalinergic input to the rat RVLM. Neurons immunorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 133 publications
2
44
0
Order By: Relevance
“…There are few, if any, connections to the dorsal motor nucleus of the vagus, but it has been suggested that some area postrema connections within the nucleus of the solitary tract are terminating on dendrites of vagal motor neurons, having cell bodies in the vagal motor nucleus (Shapiro and Miselis, 1985). Other medullary targets of the area postrema efferents are the rostral ventrolateral medulla (Blessing et al, 1987;Bowman et al, 2013), the dorsal aspect of the spinal trigeminal tract and nucleus and the paratrigeminal nucleus (Shapiro and Miselis, 1985); although Cunningham et al (1994) did not confirm these last two projections in a later study. The most prominent efferent projection of the area postrema outside the medulla is to the dorsal pontine region, the target of these fibers being the middle third of the lateral parabrachial nucleus (van der Kooy and Koda, 1983; Shapiro IV.…”
Section: Efferent Neural Connectionsmentioning
confidence: 98%
“…There are few, if any, connections to the dorsal motor nucleus of the vagus, but it has been suggested that some area postrema connections within the nucleus of the solitary tract are terminating on dendrites of vagal motor neurons, having cell bodies in the vagal motor nucleus (Shapiro and Miselis, 1985). Other medullary targets of the area postrema efferents are the rostral ventrolateral medulla (Blessing et al, 1987;Bowman et al, 2013), the dorsal aspect of the spinal trigeminal tract and nucleus and the paratrigeminal nucleus (Shapiro and Miselis, 1985); although Cunningham et al (1994) did not confirm these last two projections in a later study. The most prominent efferent projection of the area postrema outside the medulla is to the dorsal pontine region, the target of these fibers being the middle third of the lateral parabrachial nucleus (van der Kooy and Koda, 1983; Shapiro IV.…”
Section: Efferent Neural Connectionsmentioning
confidence: 98%
“…In-situ hybridization for custom synthesized and validated prepro-enkephalin (PPE) riboprobe incorporated with digoxigenin (DIG)-11-UTP (Roche Applied Science, Mannheim, Germany) was performed (final concentration 1000 ng/ml) in conjunction with fluorescent immunohistochemical (IHC) detection as described previously (Bowman et al, 2013;Kumar et al, 2010;Parker et al, 2013). No alkaline phosphatase reaction product is seen after hybridization with our PPE mRNA sense probe, or in the absence of antisense DIGriboprobes in rat spinal cord tissue (Kumar et al, 2010;Parker et al, 2013).…”
Section: 7mentioning
confidence: 99%
“…Second, other studies have reported that chemical lesions of the CeA in spontaneous hypertensive rats delay the development of hypertension (48) and attenuate cardiovascular responses to acute stress in rats with borderline hypertension (47). Most importantly, anatomic and electrophysiological studies (6,17,45,46) have identified CeA neurons that have axons projecting to presympathetic neurons in the rostral ventrolateral medulla (RVLM). The RVLM provides a key source of excitatory drive to sympathetic preganglionic neurons in the spinal cord regulating the sympathetic nervous system; therefore, it is reasonable to speculate that CeA is one of the key nuclei that plays an important role in the control of sympathetic outflow and AP in response to ethanol challenge.…”
mentioning
confidence: 99%